Pemberian Puding Tomat Pisang Ambon Terhadap Penurunan Tekanan Darah Lansia Hipertensi Di Posbindu Wilayah Kerja Puskesmas Babakan, Kota Mataram - Mutammi Desira; Ni Ketut Sri Sulendri; Fifi Luthfiyah; Suhaema Suhaema (Jurnal Gizi Prima (Prime Nutrition Journal), 2019)
Background: hypertension or high blood pressure is an increase in one's blood pressure, wherein systolic blood pressure ≥ 140 mmHg and or diastolic blood pressure ≥ 90 mmHg on repeated examinations.  Hypertension often occurs in the elderly caused by changes occurring during the aging process that cause the walls of blood vessels to undergo thickening and hardening so that it becomes stiff, the diameter of the cavity of the blood vessels shrink or Narrows. One form of non-pharmacological treatment in overcoming hypertension is by herbal medicine, namely by utilizing the content of potassium in fruits and vegetables, such as bananas and tomatoes containing high potassium that can decrease blood pressure, especially in elderly groups.Research Methods: Type of Quasy-experimental research with Pretest- Posttest with Control Group Draft. The samples in this study were elderly hypertension as many as 18 people with random techniques divided into 2 groups. Group intervention with the giving of tomato banana pudding ambon as much as 175 gram/day for 6 days, while the control group is not given treatment.Research Result: There is a decrease in systolic blood pressure as much as 17.8 mmHg (P = 0,002) and diastolic blood pressure as much as 8.9 mmHg (P = 0,347) in the intervention group.Conclusio: There is an influence on the systolic blood pressure but there is no  influence  on  diastolic blood  pressure  before  and  after  given  banana tomato pudding Ambon.